2008
DOI: 10.1098/rspb.2008.1600
|View full text |Cite
|
Sign up to set email alerts
|

Divergent trends in anadromous salmonid populations in Norwegian and Scottish rivers

Abstract: The Atlantic salmon (Salmo salar) is a charismatic anadromous fish of high conservation and economic value. Concerns have been expressed regarding the long-term viability of fisheries throughout the species's distributional range because of abundance variations that cannot currently be explained or predicted. Here, we analyse long-term catch data obtained over a wide geographical range and across a range of spatial subscales to understand more fully the factors that drive population abundance. We use rod catch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 28 publications
(32 reference statements)
1
22
0
Order By: Relevance
“…The spatial distribution of correlation coefficients is highly structured, and provides estimates of location that are consistent with known salmon feeding grounds and migration patterns3538475253. The largest contiguous areas of highest correlations, and thus most likely feeding areas, for both the 1SW and MSW components of the NE Coast mixed stock are found in the Norwegian Sea.…”
Section: Resultsmentioning
confidence: 83%
“…The spatial distribution of correlation coefficients is highly structured, and provides estimates of location that are consistent with known salmon feeding grounds and migration patterns3538475253. The largest contiguous areas of highest correlations, and thus most likely feeding areas, for both the 1SW and MSW components of the NE Coast mixed stock are found in the Norwegian Sea.…”
Section: Resultsmentioning
confidence: 83%
“…; Vøllestad et al. ) and land use (Jonsson et al. ) have been shown to influence populations of Atlantic salmonids.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Penston & Davies (2009) found that numbers of gravid females on fish farms correlated with the numbers of copepodids in surrounding waters. An increase in sea lice abundance has been linked to an increase in marine mortality of migratory salmonids, and marine salmon farming activities on Scotland's west coast have been implicated as an important contributory factor (Butler 2002, Penston et al 2004, Vøllestad et al 2009, Middlemas et al 2010, Middlemas & Armstrong 2012.…”
Section: Introductionmentioning
confidence: 99%